Digital technologies as an effective mechanism for the formation of discursive competence of future foreign language teachers (Journal of Educational Sciences, 2021)
The article examines the impact of digital technologies on a person’s professional activity and his life. Digital technologies can be actively used to improve the language training of future teachers. The results of the study on the formation of discursive competence of students – future foreign language teachers using digital technologies are presented. Discursive competence is the ability of a person to understand various types of communicative statements and to provide communication commensurate with the level of professional development of the subject of professional communication and at the same time at all levels of semantic, syntactic and extralinguistic level. The authors have developed a model and methodology for the formation of discursive competence of future foreign language teachers using digital technologies. The discursive competence included strategic and tactical, genre and textual components. The analysis of modern scientific literature made it possible to identify digital technologies, namely Web 2.0 technologies and tools, on the basis of which it is possible to form or develop the discursive competence of students of a language university: blog technology, wiki technology and podcasts. For each component-direction, exercises were selected for the development of students’ discursive competence. Thirty-nine 3rd-year students of the Kazakh Ablai Khan University of International Relations and World Languages took part in the experimental and pedagogical research. Key words: discourse, discursive competence, model, digital technologies, foreign language education, competences, professional education.